Neighborhood-level and individual-level socioeconomic status and self-reported management of ischaemic heart disease: cross-sectional results from the Korea Health Examinees Study. Issue 3 (27th March 2019) - Heo, Jongho; Oh, Juhwan; Lee, Hwa-Young; Choi, Ji-Yeob; Kim, Sujin; Subramanian, S V; Lee, Jong-Koo; Kang, Daehee
Abstract : Objective: Several studies identified neighbourhood context as a predictor of prognosis in ischaemic heart disease (IHD). The present study investigates the relationships of neighborhood-level and individual-level socioeconomic status with the odds of ongoing management of IHD, using baseline survey data from the Korea Health Examinees-Gem study. Design: In this cross-sectional study, we estimated the association of the odds of self-reported ongoing management with the neighborhood-level income status and percentage of college graduates after controlling for individual-level covariates using two-level multilevel logistic regression models based on the Markov Chain Monte Carlo function. Setting: A survey conducted at 17 large general hospitals in major Korean cities and metropolitan areas during 2005–2013. Participants: 2932 adult men and women. Outcome measure: The self-reported status of management after incident angina or myocardial infarction. Results: At the neighbourhood level, residence in a higher-income neighbourhood was associated with the self-reported ongoing management of IHD, after controlling for individual-level covariates [OR: 1.22, 95% credible interval (CI): 1.01 to 1.61). At the individual level, higher education was associated with the ongoing IHD management (high school graduation, OR: 1.33, 95% CI: 1.08 to 1.65); college or higher, OR: 1.63, 95% CI: 1.22 to 2.12; reference, middle school graduation or below). Conclusions: Our study suggests that policies or interventions aimed at improving the quality and availability of medical resources in low-income areas may associate with ongoing IHD management. Moreover, patient-centred education is essential for ongoing IHD management, especially when targeted to patients with IHD with a low education level.